A new species of Dossenus Simon, 1898 (Araneae, Trechaleidae) from Northern Brazil - Da Silva, Estevam L. Cruz; Lise, Arno A. (Zootaxa, 2011)
The genus Dossenus Simon, 1903 was revised by Silva et al. (2007) and includes two species: D. marginatus Simon, 1898 (type-species) (Trinidad-Tobago, Colombia, Peru, Brazil) and D. guapore Silva, Lise & Carico, 2007 (Panama, Colombia, Brazil). Silva & Lise (2010) recently described and illustrated the male of D. guapore from Mato Grosso do Sul, Brazil. Members of this genus are characterised by the median dark brown band on the carapace extending to the abdomen, the spoon-like shape of the median apophysis on the male palpus resembling that of Enna O. Pickard-Cambridge, 1897 and the female epigynum, which has a slightly projected scape (Silva et al. 2007).